Food Quality in Romania: ANSVSA Control and Monitoring Actions in May - September of 2022 - Iuliana CONDULEȚ; Silvius STANCIU (Communications of International Proceedings, 2022)
Within this research, control actions carried out by ANSVSA inspectors during the 2022 summer season on the Romanian seaside have been presented. The controls carried out were mainly focused on checking the implementation of the legislative requirements in force and advising the food business operators. Seven areas of tourist interest were identified at national level. During the 2022 summer season, the actions of the ANSVA command center targeted 1,996 food service and retail units. At the end of the season, 1,338 registered units were identified, the difference being represented by the number of units operating on premises which are unapproved/unregistered from a sanitary veterinary and food safety point of view and the number of rechecks. In the year 2022, the monitoring and control activity in the coastal area was intensified by increasing the number of ANSVSA teams, ensuring that occasional and permanent consumers could enjoy an adequate level of safety of food products sold on the market or in the food service sector.
Keywords: 2022 Season; Seaside; Romania; Monitoring; Control; ANSVSA